2016
DOI: 10.1038/srep38411
|View full text |Cite
|
Sign up to set email alerts
|

Distinct epigenomes in CD4+ T cells of newborns, middle-ages and centenarians

Abstract: Age-related variations in genes and microRNAs expression and DNA methylation have been reported respectively; however, their interactions during aging are unclear. We therefore investigated alterations in the transcriptomes, miRNAomes and DNA methylomes in the same CD4+T cells from newborn (NB), middle-aged (MA) and long-lived (LL) individuals to elucidate the molecular changes and their interactions. A total 659 genes showed significantly expression changes across NB, MA and LL individuals, in which we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 40 publications
1
39
0
1
Order By: Relevance
“…CD4 C T cells and CD14 C monocytes. 33,34 Such age-associated methylation changes frequently affect genes involved in immune processes which are predominantly demethylated with increasing age. [35][36][37] Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 C T cells and CD14 C monocytes. 33,34 Such age-associated methylation changes frequently affect genes involved in immune processes which are predominantly demethylated with increasing age. [35][36][37] Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…22 It may be, then, that DNA methylation of specific sites drives health behaviours rather than those behaviours modulating methylation patterns. 27 However, relatively few microRNAs are likely to be involved across different tissue types related to coreageing mechanisms, as opposed to tissue-specific types. However, DNA methylation profiles associated with these are less explored, though there is limited data linking increased methylation with age-related cataracts and coronary artery disease via oxidative stress, 23,24 and for childhood socio-economic status being associated with individual DNA methylation differences related to inflammation genes.…”
Section: Empirical Evidence For Epigenetics and Ageingmentioning
confidence: 99%
“…26 Similarly, there are strong functional network links between DNA methylation and microRNAs impacting on immune function over the lifespan. 27 However, relatively few microRNAs are likely to be involved across different tissue types related to coreageing mechanisms, as opposed to tissue-specific types. 28 Nevertheless, this is an area of considerable therapeutic interest in neurodegenerative diseases, particularly since the announcement of preliminary results from a phase II trial of an antisense oligonucleotide administered intrathecally that showed reduced huntingtin protein in Huntington disease.…”
Section: Empirical Evidence For Epigenetics and Ageingmentioning
confidence: 99%
“…While toll-like receptors (TLRs), which are activated by different subcellular molecular components (damage-associated molecular patterns, DAMPs), signal through NFκb to release several pro-inflammatory cytokines, leading to activation of the immune response, the very same NFκb constitutes an oxidative stress sensor, connecting the increased levels of ROS/RNS with activation of the inflammatory cascade [20,21]. Additionally, it must be considered that immunocompetence is usually compromised in aged individuals, and several authors have shown that this decay is closely linked to the altered epigenetic control of several immune-related genes [22][23][24]. Altogether, this evidence suggests that the difference between "normal" and pathological ageing lies in the subtle equilibrium of different homeostatic The delicate balance that sustains healthy ageing can be broken under several conditions.…”
Section: Brief Introduction To Ageingmentioning
confidence: 99%